Щодо поняття криміналістичної характеристики злочинів - Лук’янчиков, Є.; Luk’yanchikov, Е. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У науковій статті розкрито сутність кримінально-правової, кримінологічної, оперативно-розшукової ха- рактеристик злочину та на цій основі зроблено висновок, що криміналістична характеристика злочинів, вико- ристання якої може задовольнити як потреби науковців при розробці рекомендацій для розкриття злочинів, так і практичних працівників оперативних апаратів, які застосовують ці рекомендації. In the scientific article the author notes that the contemporary legal science and practice of crime investigation prove that the concepts of criminal law as well as criminological and criminal characteristics of the crime are regarded to be generally accepted phenomena nowadays. Examining the views of leading criminologists and forensic scientists the author is pertinent to note that the data of branch legal sciences as well as characteristics of the crimes can be applied in detection of crimes and modeling of private investigation techniques, but they are not separate and criminalistic in nature. The provisions of the article reveal the essence of criminal characteristics of the crime, the criminological characteristics of the crime, operational and investigative characteristics of the crime, and on this basis it is concluded that the criminological characteristics of crimes can adequately meet both the scientists’ needs in developing recommendations for crimes detection and practitioners of operational service which apply these recommendations.
On the Concept of Forensic Characteristics of Crimes
Keywords: криміналістика; злочин; характеристика; елементи; зв’язки; ознаки; forensic science; crime; the characteristic; the elements; ties; features